2007
DOI: 10.1007/s00421-007-0395-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prior heavy exercise on muscle deoxygenation kinetics at the onset of subsequent heavy exercise

Abstract: This study examines the effect of prior heavy exercise on muscle deoxygenation kinetics at the onset of heavy-intensity cycling exercise. Ten young male adults (20 +/- 2 years) performed two repetitions of step transitions (6 min) from 35 W to heavy-intensity exercise preceded by either no warm-up or by a heavy-intensity exercise. VO2 was measured breath-by-breath, and muscle deoxygenation (HHb) and total hemoglobin (Hb(tot)) were monitored continuously by near-infrared spectroscopy. We used a two-exponential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
16
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 22 publications
5
16
2
Order By: Relevance
“…average NIRS; Refs. 15,16,33,44). However, the present finding of a slower of the primary component during subsequent heavy exercise is not consistent with previous studies that found a similar for bout 1 vs. bout 2 (16,32,33,44).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…average NIRS; Refs. 15,16,33,44). However, the present finding of a slower of the primary component during subsequent heavy exercise is not consistent with previous studies that found a similar for bout 1 vs. bout 2 (16,32,33,44).…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, a rapid appearance of phase II of mQ would occur in regions where the early increase in mQ closely matches the dynamics of mV O 2 (i.e., constant deoxy-[HbϩMb]), and thereby a short TD would be followed by a slower (20). The results in the present study support the latter scenario, thus suggesting that the performance of prior heavy exercise would promote the convective delivery of O 2 (phase II mQ ) to multiple sites of the muscles, improving the adequacy of mV O 2 /mQ O 2 matching at the onset of the subsequent bout of exercise (7,9,15,16,22,23,44).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations